Ekwǫ̀ and Tłı̨ chǫ Nàowo / Caribou and Tłı̨ chǫ language, culture and way of life: An evolving relationship and shared history - Zoe, John B. (Rangifer, 2012)
This paper is adapted from the author’s contribution to the NACW presentation co-authored with Kerri Garner and Jan Adamczewski, “Tłįchǫ People and Ekwǫ̀ (Caribou): An Evolving Relationship And Shared History,” as well as contributions to the NACW Aboriginal Talking Circles. We are now going to go back in time to long before co-management was even contemplated and before the Government of the Northwest Territories existed, back to the pre-colonial relationship between Tłı̨ chǫ and ekwǫ̀ . We will consider how this has changed over time, with our people being influence.